An Overview of the Double Burden of Malnutrition in Toddlers and Its Implications for Cardiovascular Disease Risk in Adulthood - Brigitte Sarah Renyoet; Sarah Melati Davidson; Priskyla Octavina Suryana (Indonesian Health Issue, 2026)
Adi, A. C. (2016). Karbohidrat. In Hardinsyah & I. D. N. Supariasa (Eds.), Ilmu Gizi Teori dan Aplikasi (pp. 25–36). EGC Penerbit Buku Kedokteran.Aisah, S., Dewi Ngaisyah, R., & Rahmuniyati, M. E. (2019). Personal hygiene and environment sanitation related with stunting at Wukirsari Village Cangkringan Sub-District. Prosiding Seminar Nasional Multidisiplin Ilmu , 1(2), 49–55.Alhuneafat, L., Jabri, A., Omar, Y. A., Margaria, B., Al-abdouh, A., Mhanna, M., Shahrori, Z., Hammad, N., Rayyan, A., Nasser, F., Kondapaneni, M., & Siraj, A. (2022). Relationship between body mass index and outcomes in acute myocardial infarction. Journal of Clinical Medicine Research, 14(11), 458–465. Allai, F. M., Gul, K., Zahoor, I., Ganaie, T. A., Nasir, G., & Azad, Z. R. A. A. (2021). Malnutrition: impact of zinc on child development. In Microbial Biofertilizers and Micronutrient Availability: the Role of Zinc in Agriculture and Human Health (pp. 83–100). Springer International Publishing.Amadu, I., Seidu, A. A., Duku, E., Frimpong, J. B., Hagan Jnr., J. E., Aboagye, R. G., Ampah, B., Adu, C., & Ahinkorah, B. O. (2021). Risk factors associated with the coexistence of stunting, underweight, and wasting in children under 5 from 31 Sub-Saharan African countries. BMJ Open, 11(12), 1–10. Animasahun, B. A., & Itiola, A. Y. (2021). Iron deficiency and iron deficiency anaemia in children: physiology, epidemiology, aetiology, clinical effects, laboratory diagnosis and treatment: literature review. In Journal of Xiangya Medicine (Vol. 6, Number 22, pp. 1–14). AME Publishing Company.Antono, S. D. (2017). The difference in learning achievement between obese and non-obese students in elementary school students in Kediri City. Journal of Health Sciences, 5(2), 84–90.Astuti, N. F. W., Huriyati, E., & Susetyowati. (2020). The prevalence and determinants of household dual burden malnutrition in Indonesia. Indonesian Public Health Media, 16(1), 100–115. https://doi.org/10.30597/mkmi.v16i1.9064Baculu, E. P. H. (2017). Hubungan pengetahuan ibu dan asupan karbohidrat dengan status gizi pada anak balita. Promotif, 7(1), 14–17.Badan Kebijakan Pembangunan Kesehatan. (2023). Survei Kesehatan Indonesia (SKI) 2023 dalam Angka. Kementerian Kesehatan Republik Indonesia.Budiman, Sihombing, R., & Pradina, P. (2015). Hubungan dislipidemia, hipertensi dan diabetes melitus dengan kejadian infark miokard akut. Jurnal Kesehatan Masyarakat Andalas, 10(1), 32–37. http://jurnal.fkm.unand.ac.id/index.php/jkma/Çelik, N. (2019). The prevalence of subclinical hypothyroidism in obese children and adolescents and its effects on metabolic parameters. Cumhuriyet Medical Journal, 41(4), 691–697. https://doi.org/10.7197/cmj.vi.551051Darawati, M. (2016). Gizi Ibu Hamil. In Hardinsyah & I. D. N. Supariasa (Eds.), Ilmu Gizi Teori dan Aplikasi (pp. 170–181). EGC Penerbit Buku Kedokteran.Deng, S. A., & Setiarini, A. (2022). Analisis kebiasaan mencuci tangan dan faktor sanitasi lingkungan dengan kejadian diare pada balita di wilayah kerja Puskesmas Kalideres, Jakarta Barat 2022. The Indonesian Journal of Health Promotion, 5(10), 1255–1262. https://doi.org/10.31934/mppki.v2i3Doloksaribu, R. (2016). Lemak. In Hardinsyah & I. D. N. Supariasa (Eds.), Ilmu Gizi Teori dan Aplikasi (pp. 51–58). Penerbit Buku Kedokteran EGC.Evans, E. W., & Redmond, E. C. (2019). Domestic kitchen microbiological contamination and self-reported food hygiene practices of older adult consumers. Journal of Food Protection, 82(8), 1326–1335.Fajrina, N., & Syaifudin, S. (2016). Hubungan faktor ibu dengan kejadian stunting pada balita di Puskesmas Piyungan Kabupaten Bantul. Universitas ‘Aisyiyah Yogyakarta.Farah, A. M., Nour, T. Y., Endris, B. S., & Gebreyesus, S. H. (2021). Concurrence of stunting and Overweight/Obesity Among Children: Evidence from Ethiopia. PLoS ONE, 16(1), 1–17.Fithra, H., & Siska, D. (2020). The correlation between environmental sanitation and stunting case in Pidie District. International Journal on Advanced Science Engineering Information Technology, 10(3), 1214–1220.Fitri, N. L., Sari, S. A., Dewi, N. R., Ludiana, & Nurhayati, S. (2022). The relationship between maternal age and the incidence of SEZ in pregnant women in the working area of the Ganjar Agung Health Center, West Metro District, Metro City. Journal of Health Discourse, 7(1), 26–31.Hamid, N. A., Hadju, V., Dachlan, D. M., Jafar, N., & Battung, S. M. (2020). The relationship between exclusive breastfeeding and the nutritional status of children aged 6-24 months in Timbuseng Village, Gowa Regency. JGMI: The Journal of Indonesian Community Nutrition, 9(1), 51–62.Hossain, F. B., Shawon, M. S. R., Al-Abid, M. S. U., Mahmood, S., Adhikary, G., & Bulbul, M. M. I. (2020). Double burden of malnutrition in children aged 24 to 59 months by socioeconomic status in five South Asian countries: Evidence from demographic and health surveys. BMJ Open, 10(3), 1–12. Hussain, D., & Biswas, B. (2024). Understanding the impact of socio-economic factors on child malnutrition in India with an emphasis on no-toilet facilities: Evidence from national family health surveys. GeoJournal, 89(1), 1–20. Inayatullah, K. R., Djokosujono, K., & Ramadhan, R. P. (2022). Karakteristik kabupaten dan kota di Indonesia dengan masalah gizi pada penduduk dewasa tahun 2018. Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 5(5), 519–529.Jannah, M., & Nadimin. (2021). Riwayat Kekurangan Energi Kronis (KEK) pada ibu dan kejadian stunting pada balita di wilayah kerja Puskesmas Turikale. Media Kesehatan Politeknik Kesehatan Makassar, 16(1), 343–352. Khaliq, A., Wraith, D., Nambiar, S., & Miller, Y. (2022). A review of the prevalence, trends, and determinants of coexisting forms of malnutrition in neonates, infants, and children. BMC Public Health, 22(1), 1–23. Khan, A. Y., Fatima, K., & Ali, M. (2021). Sanitation ladder and undernutrition among under-five children in Pakistan. Environmental Science and Pollution Research, 28(29), 38749–38763. https://doi.org/10.1007/s11356-021-13492-7Lestari, P., Trimawati, Sparwati, M., Prabowo, H., & Yarisma, F. W. (2023). Waspada stunting itu penting. Jurnal Pengabdian Mandiri, 2(6), 1233–1236. Li, H., Yuan, S., Fang, H., Huang, G., Huang, Q., Wang, H., & Wang, A. (2022). Prevalence and associated factors for stunting, underweight and wasting among children under 6 years of age in rural Hunan Province, China: a community-based cross-sectional study. BMC Public Health, 22(1), 1–12. Mogensen, K. M. (2017). Essential fatty acid deficiency. In Pract Gastroenterol (Vol. 41, Number 6, pp. 37–44).Monge, M. F. E., Hinojal, M. C. T., Barrado, E., Monge, M. A. E., & Miguelsanz, J. M. M. (2021). Zinc nutritional status in a series of children with chronic diseases: A cross-sectional study. Nutrients, 13(4), 1–16. https://doi.org/10.3390/nu13041121Mutika, W., & Syamsul, D. (2018). Analisis permasalahan status gizi kurang pada balita di Puskesmas Teupah Selatan Kabupaten Simeuleu. Jurnal Kesehatan Global, 1(3), 127–136.Mutumba, R., Pesu, H., Mbabazi, J., Greibe, E., Olsen, M. F., Briend, A., Mølgaard, C., Ritz, C., Nabukeera-Barungi, N., Mupere, E., Filteau, S., Friis, H., & Grenov, B. (2023). Correlates of iron, cobalamin, folate, and vitamin A status among stunted children: a cross-sectional study in Uganda. Nutrients, 15(15), 1–13. Mythili, S., & Malathi, N. (2015). Diagnostic markers of acute myocardial infarction. Biomedical Reports, 3(6), 743–748. https://doi.org/10.3892/br.2015.500Ong, Y. Y., Pang, W. W., Michael, N., Aris, I. M., Sadananthan, S. A., Tint, M. T., Liang Choo, J. T., Ling, L. H., Karnani, N., Velan, S. S., Fortier, M. V, Tan, K. H., Gluckman, P. D., Yap, F., Chong, Y. S., Godfrey, K. M., Chan, S. Y., Eriksson, J. G., Chong, M. F. F., & Lee, Y. S. (2023). Timing of introduction of complementary foods, breastfeeding, and child cardiometabolic risk: a prospective multiethnic Asian cohort study. American Journal of Clinical Nutrition, 117(1), 83–92. Owa, K., Putra, I. W. G. A. E., & Windiani, I. G. A. T. (2017). Risk factors for low birth weight infants in East Nusa Tenggara. Public Health and Preventive Medicine Archive, 5(1), 39–43. https://doi.org/10.15562/phpma.v5i1.40Pereira, J. K. G., Moraes, R. C. S., Sawaya, A. L., Alves, J. L. D. B., Filgueiras, A. R., Franco, M. D. C. P., & Martins, V. J. B. (2023). High glycemia and resistin normalized in children with double burden of malnutrition: a cross-sectional study. Applied Physiology, Nutrition, and Metabolism, 49(1), 114–120.Pusmaika, R., Novfrida, Y., Simatupang, E. J., Djami, M. E. U., & Sumiyati, I. (2021). The relationship between maternal age during pregnancy and the incidence of stunting in toddlers in Tangerang Regency. Indonesian Health Issue, 1(1), 49–56.Qolbiyah, F. N., Yudia, R. C. P., & Aminyoto, M. (2021). The relationship between feeding practices and the incidence of stunting in toddlers at the Barong Tongkok Health Center, West Kutai Regency. Journal of Science and Health, 3(6), 853–863. https://doi.org/10.25026/jsk.v3i6.901Rahmawati, N. F., Fajar, N. A., & Idris, H. (2020). Social, economic, and utilization factors of posyandu with the incidence of stunting under five poor families of PKH recipients in Palembang. Indonesian Journal of Clinical Nutrition, 17(1), 23–33. Rukmana, E., Briawan, D., & Ekayanti, I. (2016). Faktor risiko stunting pada anak usia 6-24 bulan di Kota Bogor. Jurnal MKMI, 12(3), 192–199.Salari, N., Morddarvanjoghi, F., Abdolmaleki, A., Rasoulpoor, S., Khaleghi, A. A., Hezarkhani, L. A., & Mohammadi, M. (2023). The global prevalence of myocardial infarction: a systematic review and meta-analysis. BMC Cardiovascular Disorders, 23(1), 1–12.Saleh, S. N. H., Muzayyana, M., Sarman, S., & Mokodompit, H. K. (2022). Hubungan pemberian MP-ASI dengan status gizi balita 1 tahun di UPTD Puskesmas Pinolosian. Madani: Jurnal Ilmiah Multidisiplin, 1(1).Samikannu, S. R., & Palanivelu, S. K. (2019). Study of myocardial function in children with severe acute malnutrition. International Archives of Integrated Medicine, 6(3), 132–136. Samuel, A., Osendarp, S. J. M., Feskens, E. J. M., Lelisa, A., Adish, A., Kebede, A., & Brouwer, I. D. (2022). Gender differences in nutritional status and determinants among infants (6-11 m): a cross-sectional study in two regions in Ethiopia. BMC Public Health, 22(1), 1–12. https://doi.org/10.1186/s12889-022-12772-2Shlisky, J., Mandlik, R., Askari, S., Abrams, S., Belizan, J. M., Bourassa, M. W., Cormick, G., Driller-Colangelo, A., Gomes, F., Khadilkar, A., Owino, V., Pettifor, J. M., Rana, Z. H., Roth, D. E., & Weaver, C. (2022). Calcium deficiency worldwide: prevalence of inadequate intakes and associated health outcomes. Annals of the New York Academy of Sciences, 1512(1), 10–28. Sinaga, F. R., Heriyani, F., & Khatimah, H. (2016). Hubungan kondisi ventilasi rumah dengan kejadian TB paru di wilayah Puskesmas Kelayan Timur. Berkala Kedokteran, 12(2), 279–288.Sofiah, W., & Roswah, L. F. (2022). Asuhan keperawatan pasien yang mengalami infark miokard akut dengan nyeri melalui teknik relaksasi nafas dalam. Jurnal Keperawatan Muhammadiyah Bengkulu, 10(1), 78–83. Soumokil, O. (2017). Hubungan asupan energi dan protein dengan status gizi anak balita di Kecamatan Nusalaut Kabupaten Maluku Tengah. Global Health Science, 2(4), 341–350.Sukmasari, T. N., & Renyoet, B. S. (2023). Literature review: Diet and risk of Acute Myocardial Infarction (IMA). Journal of Nutrition and Culinary, 3(2), 44–53.Swathma, D., Lestari, H., & Ardiansyah, R. T. (2016). Analysis of risk factors for BBLR, infant body length at birth and history of basic immunization against stunting incidence in toddlers aged 12-36 months in the working area of Kandai Health Center, Kendari City in 2016. Scientific Journal of Unsyiah Public Health Students, 1(3), 1–10.Talpur, S., Afridi, H. I., Kazi, T. G., & Talpur, F. N. (2018). Interaction of lead with calcium, iron, and zinc in the biological samples of malnourished children. Biological Trace Element Research, 183(2), 209–217. United Nations Children’s Fund, World Health Organization, & World Bank Group. (2023). Levels and trends in child malnutrition.Wang, J., Wu, Y., Xiong, G., Chao, T., Jin, Q., Liu, R., Hao, L., Wei, S., Yang, N., & Yang, X. (2016). Introduction of complementary feeding before 4 months of age increases the risk of childhood overweight or obesity: A meta-analysis of prospective cohort studies. Nutrition Research, 36(8), 759–770. Wardani, K., & Renyoet, B. S. (2022). Literature study: Estimation of potential economic loss due to undernutrition in Indonesia. JGK, 14(1), 114–127.Wijaya, F. A. (2019). Exclusive breastfeeding: Ideal nutrition for babies 0-6 months. Mirror of the World of Medicine, 46(4), 296–300.Wijhati, E. R., Nuzuliana, R., & Pratiwi, M. L. E. (2021). Analysis of nutritional status in stunting toddlers. Journal of Midwifery, 10(1), 1–12. Yanti, E. M. (2023). The relationship between economic factors and parental parenting with the incidence of stunting in toddlers in Kembang Kerang Daya Village. Journal of Mandalika Transformation, 4(8), 466–475.Zeffira, L., Defiari Putri, S., & Dewi, N. P. (2022). Maternal pregnancy profile on the incidence of stunting in children aged 6-24 months in the working area of the Padang City Cold Air Health Center. SCIENCE, 1(3), 190–197.Zhang, Y. Q., Li, H., Wu, H. H., & Zong, X. N. (2021). Stunting, wasting, overweight and their coexistence among children under 7 years in the context of the social rapidly developing: Findings from a population-based survey in nine cities of China in 2016. PLoS ONE, 16(1), 1–15. Zhu, J., Su, X., Li, G., Chen, J., Tang, B., & Yang, Y. (2014). The incidence of acute myocardial infarction in relation to overweight and obesity: A meta-analysis. Archives of Medical Science, 10(5), 855–862.